Influence of water quality on benthic macroinvertebrates in a groundwater-dependent wetland - Banda, Kawawa; Ngwenya, Victoria; Mulema, Mataa; Chomba, Innocent; Chomba, Machaya; Nyambe, Imasiku (Frontiers in Water, 2023)
Benthic invertebrates communities are frequently used as indicators of aquatic ecosystem health since many species are sensitive to pollution and abrupt changes in their environment. Limited knowledge exists on the interlinkages of hydrological dynamics, water quality and the ecological character of groundwater-dependant ecosystems especially in developing countries. In this study we assessed the sensitivity of benthic macroinvertebrates to water quality dynamics in the Barotse Floodplain, a groundwater-dependant wetland. Benthic invertebrates were sampled in the dry season using the kick-net method at selected points upstream, mid-stream and downstream. The selection of sampled points was based on an initially conducted water quality survey that characterised the wetland into mainly two water types, NaHCO3 (upstream) and CaMgHCO3 (downstream). Canonical Correspondence Analysis (CCA) was used to investigate the influence of water quality on macroinvertebrate subclass-taxa level. Furthermore, factor analysis was used to derive the processes propagating the observed water quality variability. It was established that the composition and diversity of macroinverbrate communities at subclass-taxa level was influenced by effects of the wetland flood pulse, salinity (mineralisation) from groundwater input and biogeochemical processes during the expansion and contraction of the floodplain-river exchange. This study has demonstrated that biomonitoring was effective in capturing the natural processes/regimes of the environmental (such as flooding) and thus has potential to be used for mointoring extreme effects of phenomenon such as climate change. It is recommended that, the families, genus and species taxonomic levels are needed to improve the understanding of responses of the subclass-taxa level and the detection of specific contamination signatures, to ensure wetland conservation and protection. Integrated water resources management for wetlands thus should incorporate biomonitoring conjuctively with traditional methods to ensure vital ecosystems are not compromised at the expense of maximising the economic and social welfare of humanity.